Contemporary Issues in Nigerian Law: Essays in Honour of Professor Elisabeta Smaranda Olarinde, FCAI, FCArb (Lawlexis International, Lagos, 2023) - Osondu-Oti, Adaora; Olubiyi, Ifeoluwa A.; Olarinde-Olomola, Omolola; Adeniran, Afolalu Sunday; Adeniran, Abraham; Adesina, Adetola (Journal of Sustainable Development Law and Policy, 2024)
It is indeed an honour for us to review this book titled CONTEMPORARY ISSUES IN NIGERIAN LAW: ESSAYS IN HONOUR OF PROFESSOR ELISABETA SMARANDA OLARINDE, FCAI, FCArb; a book written in celebration of a legal amazon and astute university Administrator, Professor Elisabeta Smaranda Olarinde. Prof. E. S. Olarinde has lived a life of excellence and impact with her over 40 years’ experience at the Nigerian Bar, 40 years of it as a law teacher, a mother and seasoned university Administrator. She has served humanity and given her best to the society and she is still actively doing so in her various roles including that of being the Vice chancellor of Afe Babalola University, Ado-Ekiti (ABUAD), Nigeria, a foremost university ranked by Times Higher Education Impact Rankings Number 1 University in Nigeria for three consecutive years (2022, 2023 & 2024).